The reasons behind the increasing wage inequality in Mexico - Meza González, Liliana (2004)
Using data from the National Urban Employment Survey, 1988-1999, this paper tries to separate the local and the national forces behind the increasing wage inequality in Mexico. The paper analyzes the trend of 3 different inequality measures in 16 different local labor markets and shows that the rising Mexican wage inequality is concentrated in the southern and central cities, while northern border cities seem to have experienced significant drops in wage inequality. Using the variability in the inequality measures at a local level, the analysis combines cross section and time series data to understand the role that local demographic, industrial and economic characteristics have played in the rising inequality. Drops in local economic activity, employment in the service sector, and occupational opportunities for executives seem to be positively correlated with the rising wage inequality, while occupational opportunities for moderately educated workers seem to be negatively correlated with it. Specialization of the local economies in the production of tradable goods shows contradicting results and no conclusion can be drawn from them.